Investigation of a binary eutectic mixture of phase change material for building integrated photovoltaic (BIPV) system - Karthick, A.; Murugavel, K. Kalidasa; Ghosh, Aritra; Sudhakar, K.; Ramanan, P. (Elsevier B.V., 2020)
The incorporation of phase change material (PCM) into the building integrated semi-transparent photovoltaic (BISTPV) system is a promising technology to regulate the enhanced surface temperature of the photovoltaic (PV) system. In this work, Sodium Sulfate Decahydrate (Na2SO4·10H2O) and Zinc Nitrate Hexahydrate (N2O6Zn·6H2O) were mixed to form the binary eutectic PCM by heating mixing method. The results of Differential Scanning Calorimeter (DSC) characterization of those eutectic mixtures showed that the molar mass proportion of 70% weight of Na2SO4·10H2O and 30% weight N2O6Zn·6H2O was an optimum eutectic mixture for the solar energy applications. The developed eutectic mixture was employed in the specially designed and fabricated building-integrated semi-transparent photovoltaic phase change material (BISTPV-PCM) system to regulate BISTPV cell temperature. The experimentation was carried out at the outdoor environmental conditions in the region of Kovilpatti (9°10′0″N, 77°52′0″E), Tamilnadu, India throughout the year of 2018. The instantaneous peak temperature was reduced up to 12 ᵒC for the BISTPV-PCM system compared to the non-PCM counterpart. The annual output power generated from the BISTPV module was 34,287 W h/year which increased to 37,024 W h/year by using PCM.